PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP COST OF DEBT DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Uswatun Hasanah, Usi; Aziza, Nurna; Aisyah, Siti (JURNAL FAIRNESS, 2021)
This study aims to examine the effects of corporate social responsibility on the cost of debt with profitability as an intervening variable. Corporate Social Responsibility (CSR) in this study is measured by the Corporate Social Disclosure Index (CSDI) with GRI standards as a reference, cost of debt is measured by interest expense for the current year divided by average debt and profitability is measured by ROE. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 with purposive sampling technique. The sample used in this study were 74 manufacturing companies with a total of 222 observations.         This research is classified in quantitative research.The statistical analysis tool used to test the hypothesis in this study is Smart PLS 3.0. The results of this study indicate that CSR has a negative effect on cost of debt and profitability has been shown to be able to mediate the effect of CSR on cost of debt.